(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This study investigates the types and motivations of cyberbullying expressions used by Twitter users in the Selena Gomez and Hailey Bieber drama. Employing a descriptive qualitative approach, the research analyses transcripts of Twitter comments to understand the underlying motives behind the observed bullying behaviour. The findings have revealed several key motives including fanaticism towards idols. Strong identification with and defence of preferred idols can induce aggressive responses towards perceived threats, leading to attacks on rival fans or their idols. Emotional reactivity that encouuunters tweets perceived as disrespectful or harmful towards their idols can trigger anger and frustration, driving users to engage in cyberbullying as a means of retaliation. Witnessing the success or popularity of other idol groups or their fans can trigger feelings of jealousy, prompting some users to engage in cyberbullying to diminish their rivals’ perceived advantages. Engaging in aggressive online behaviour and "winning" arguments against perceived opponents can provide some users with a sense of validation and satisfaction, further reinforcing the cycle of cyberbullying.